1970
DOI: 10.1111/j.1365-2141.1970.tb01630.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vincristine on the Platelet Count in Rats

Abstract: Summary. The effect of vincristine on the platelet count of rats is described. It was found that, depending upon dosage, the drug can cause either a thrombocytosis or marrow hypoplasia with thrombocytopenia in normal rats. Thrombocytosis was found even after prolonged treatment with vincristine when this was given at appropriate dosage. The thrombocytosis promoting effect of the drug was not enhanced by an increase in the splenic platelet pool or decreased by splenectomy. However, it was abolished when prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
3

Year Published

1972
1972
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 5 publications
2
15
3
Order By: Relevance
“…The biphasic dose response and the timecouirse of these changes are also similar to those observed with Colcemid (25). The most pronounced thrombocytosis is observed with doses close to the minimutm dose requiired to prodtuce an effect (19)(20)(21)(22)(23)(24)(25). However, at higher dosage an early thrombocytopenia is followed by a late reactive thrombopoietic response.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The biphasic dose response and the timecouirse of these changes are also similar to those observed with Colcemid (25). The most pronounced thrombocytosis is observed with doses close to the minimutm dose requiired to prodtuce an effect (19)(20)(21)(22)(23)(24)(25). However, at higher dosage an early thrombocytopenia is followed by a late reactive thrombopoietic response.…”
Section: Resultssupporting
confidence: 54%
“…In laboratory animals the transition from maximum thrombocytosis to thrombocytopenia is observed over a twofold range of vincristine dosage (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In contrast, in the present study thrombocytopenia was not observed over a sevenfold increase in Colcemid dosage.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…This reaction to miconazole administration may be similar to that described after the administration of vinca alkaloids in experimental animals or in humans (4,(6)(7)(8)10). It is possible that the impressive increase of peripheral platelets was related to mobilization of splenic thrombocytes, but such a mechanism remains speculative.…”
Section: Resultsmentioning
confidence: 65%